Review paperTuberculosis of the oral cavity: an uncommon but still a live issue - Krawiecka, Ewa; Szponar, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
This paper aims at characterizing clinical features, occurrence, diagnostic process and treatment of oral tuberculosis (TB), basing on the available literature. Oral TB manifestations are uncommon and usually secondary to pulmonary changes. They predominantly appear as ulcers. Eruptions are usually single, painful and resistant to conventional treatment. Diagnosis always needs to be confirmed histopathologically. Anti-tubercular systemic therapy is required in every patient diagnosed with oral TB, while topical treatment is only adjuvant. A low incidence of oral TB together with a non-specific clinical picture might pose difficulties in its diagnosis. Oral changes in TB are likely to be overlooked what can result in further spread of Mycobacterium tuberculosis due to a delay in instituting proper treatment. Tuberculosis morbidity has risen recently and more multi-drug resistant strains of TB bacilli are found, what can result in a higher incidence of oral TB. Clinicians should be therefore aware of a possible occurrence of this entity and consider it while making a differential diagnosis of atypical oral changes.